PENDEKATAN TEORI AKUNTANSI POSITIF DALAM KASUS DERIVATIF PT. INDOSAT - Theresia Hesti Bwarleling (Universitas Bunda Mulia, 2017)
Through a positive approach to the theory of accounting, this article attempts to discuss the case of a derivative PT Indosat, which took place in 2007. In philosophy, the goal of positive accounting theory is to explain and predict the occurrence of practices - practices accepted accounting principles. Positive accounting theory tries to examine why the selection principle - the accounting principles used by practitioners in some corporate environments. Three hypotheses used in applying positive accounting theory is a hypothesis of bonus plans, debt Testament hypothesis, and assuming the political process. In the case of a derivative PT Indosat expected happened over tax evasion, so discussion paper will pay more attention to the third hypothesis, namely political hypothesis value process.Key words : Positive Accounting Theory, Derivative, Political Cost.